Synthesis, characterization and biological activity of some nickel(II) mixed ligands complexes of dithiocarbamate and 1,10-phenanthroline - Abbas, Salih Hamza (European Journal of Chemistry, 2017)
Two ligands; pyrrolidine-1-carbodithioate sodium (L1) and piperidine-1-carbodithioate sodium salt(L2) and their nickel(II) mixed ligands complexes with 1,10-phenanthroline (L3) have been synthesized and characterized by FT-IR, UV-visible,1H NMR spectra. The biological activities of these complexes were also evaluated. The spectral data indicated that the 1,10-phenanthrolineand dithiocarbamate ligands are considered as a bidentate nitrogen and sulfur ligands, respectively. The study suggested that the above ligands formed complexes of general formula [Ni(Lx)2(L3)1] and [Ni(Lx)1(L3)2]Cl (x=1 or 2) mononuclear (monomer) complexes. The complexes show moderate and selective activity against tested microorganisms.